Economic Evaluation of Petra Site in Jordan by Using Travel Cost Method - Haddad, Akram Masoud (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2010)
Hidden behind an almost impenetrable barrier of rugged mountains, the rock-carved city of Petra is full of mysterious charm. Petra is located at about 300 km to the south of Amman, the capital of Jordan announced in 2007 as one of the new world wonders, In this paper the travel cost method (TCM) that uses the costs incurred by individuals traveling to reach a site as a proxy for its recreation value, in the determination of economic value historical site of Petra. A sample of 1590 visitors to the site during 2008 was asked about the costs incurred per visit and frequency of visiting the Petra city. Thus, the recreation value of the site was estimated at about (1.8) thousands million JD (1JD=1.4 $US). Such information is expected to help policy makers in any future decisions to be taken for the improvement of the Petra site.